EFFECT OF EYE AND FEET COORDINATION, STRENGHT, SPEED ON PASSING ACCURACY IN SSB KABAN JAHE - Julmi Akmal; Sanusi Hasibuan; Agung Sunarno (Indonesia Sport Journal, 2022)
The problem in this study is the importance of physical conditions in influencing passing accuracy. The purpose of the study was to determine the direct effect of eye and foot coordination, strength on speed in soccer games. The method used in this research is descriptive and varied methods, the research sample is 30 people. The instruments used are passing accuracy test instruments, eye and foot coordination tests, strength tests using a leg and back dynamometer. The data analysis technique used is path analysis. This study involves 3 independent variables whose influence on the dependent variable will be investigated, namely soccer passing accuracy (X4), the independent variables are eye and foot coordination (X1), strength (X2) and speed (X3). Research Results: 1. There is a direct effect of eye and foot coordination on speed in soccer games. 2. There is an indirect effect of strength on speed in soccer games. 3. There is an indirect effect of eye and foot coordination on passing accuracy in soccer games. 4. There is a direct influence of strength on passing accuracy in soccer games. 5. There is an indirect effect of soccer speed on passing accuracy in soccer games. 6. There is an indirect effect of eye-foot coordination on strength in soccer games. 7. There is a direct effect of eye-foot coordination through strength on passing accuracy in soccer games. 8. There is a direct effect of eye-foot coordination through speed on passing accuracy in soccer games. 9. There is an influence of strength through speed on passing accuracy in soccer games.Keywords: Coordination, Speed, Strength